Supporting the right workplace experience: A dynamic evaluation of three activation programmes for young job seekers in Slovakia - Miroslav Štefánik; Lukáš Lafférs (Journal for Labour Market Research, 2024)
This paper investigates three alternative active labour market policy programmes available to young job seekers in Slovakia who were registered in 2011. All of the programmes facilitate gaining work experience and share a comparable design; however, they differ mainly in the collected workplace experience and the composition of participants. Using administrative data, we first explore the selection into each programme; second, we estimate the treatment effects on job seekers' postparticipation absence from the registry of the unemployed. For this we argue that we have sufficiently rich data to control for selection into programs. We use a dynamic estimator and report the average treatment effects of participation in different periods between the sixth and fifteenth month after starting unemployment. For participation in earlier stages of unemployment, we confirm differences in the programmes impacts, with patterns described by previous literature; workplace experience collected in either the private sector or in a regular workplace appears to improve the chances of absence from registered unemployment of young job seekers relatively more than does participation in a public works type of programme. When compared later in the unemployment spell, the between-programme differences level out. Despite its ambivalent average impact, the public works type of programme positively impacts specific subgroups of participants.
Keywords: C21; D04; J08; 330; Unemployment; Impact evaluation; Active labour market policy (ALMP); Youth activation